Analisis Faktor Yang Berpengaruh Terhadap Pertumbuhan Usaha Pelaku Usaha Kecil - Retnaningdiah, Dian (Kajian Ekonomi dan Bisnis, 2019)
The challenges of global business world will give impacts on enterprises in Indonesia, involving Micro Small and Medium Enterprises. The objective of this research is to find out the effect of Islamic micro finance towards the development of MSMEs in Sleman, Special Region of Yogyakarta. The 30 people of respondents are selected by using purposive random sampling method. Validity and reliability tests give a result in which each answered question is valid and reliable. Analytical regression result shows that Islamic micro finance variable has a siginificant impact on enterprises’ development. This is showed by the independent variable significance score that is lower than the used alpha (5%).